Class and the post-Fordist work ethic: Subjects of passion and subjects of achievement in the work society. Issue 5 (September 2019) - Farrugia, David
This article explores how the 'post-Fordist work ethic' contributes to the formation of classed subjectivities. Drawing on the work of Kathi Weeks, the article approaches the post-Fordist promise of self-realisation through work in terms of the individualised accrual of value that has become so central to the experience of class within the cultural politics of neoliberalism. Empirically, the article draws on a programme of research on the formation of young workers to describe two ideal typical manifestations of the post-Fordist work ethic, characterised as 'subjects of achievement' and 'subjects of passion', which reflect classed differences in the way that self-realisation through work is defined and experienced. In this way, the article argues that the contemporary work ethic is inflected with forms of class distinction that pre-date the shift to post-Fordism, and that these distinctions within the post-Fordist work ethic are critical to classed modes of contemporary subjectification. This differentiation reflects the ideological history of work and class under capitalism as well as the promise of individualised self-realisation that is so critical to subject formation in the post-Fordist present.